Bio-mechanical aspects of elite cyclists' motor system adaptation in process of competition activity - A.N. Kolumbet; S.G. Natroshvili; T.G. Babyna (H.S. Skovoroda Kharkov National Pedagogical University, 2017)
Purpose; to study the laws of motor structure adaptation of elite cyclists, specializing in 4 km individual pursuit racing on track. Material: in the research 18 elite athletes participated. We studied special aspects of athletes' coordination structure in experiment, which simulated competition activity. Results: at start segment of distance high speed depends on effectiveness of right leg's pulling; on pressing and pushing of left leg. At initial stage of distance high efficiency of pedaling is ensured by pressing and pulling of right and left legs. At middle segment high workability depends on movement of right leg; pressing, pulling and pushing of left leg. On finish speed depends by effectiveness of pressing, pulling and moving of right leg; pressing and pulling of left leg. Conclusions: the presented material creates real pre-conditions for development of bio-mechanical models of cyclists' pedaling technique. The received data can be used for special searching of optimal movement, considering competition tactic. The received results can be used for choosing of means and methods of athletes' movements' pedagogic re-constructions.